2021
DOI: 10.1186/s12931-021-01790-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation and minimum important difference of the UCSD Shortness of Breath Questionnaire in fibrotic interstitial lung disease

Abstract: Rationale The University of California, San Diego Shortness of Breath Questionnaire (UCSDSOBQ) is a frequently used domain-specific dyspnea questionnaire; however, there is little information available regarding its use and minimum important difference (MID) in fibrotic interstitial lung disease (ILD). We aimed to describe the key performance characteristics of the UCSDSOBQ in this population. Methods UCSDSOBQ scores and selected anchors were measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Disease progression was defined as a relative decline of ≥ 10% in FVC, or a relative decline in FVC of ≥ 5% and one of the three additional criteria: (1) a decline in diffusion capacity to carbon monoxide (DLCO) ≥ 15%; (2) increased fibrosis on HRCT; (3) progressive symptoms, or progressive symptoms and increased fibrosis on HRCT over 24 months despite treatment [ 26 ]. The progressive symptoms were defined as increased (SGRQ, SOBQ) or decreased (LCQ) total scores of a minimum clinically significant difference of the questionnaires [ 27 29 ]. The information of progression on HRCT was collected from all the HRCTs available during follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease progression was defined as a relative decline of ≥ 10% in FVC, or a relative decline in FVC of ≥ 5% and one of the three additional criteria: (1) a decline in diffusion capacity to carbon monoxide (DLCO) ≥ 15%; (2) increased fibrosis on HRCT; (3) progressive symptoms, or progressive symptoms and increased fibrosis on HRCT over 24 months despite treatment [ 26 ]. The progressive symptoms were defined as increased (SGRQ, SOBQ) or decreased (LCQ) total scores of a minimum clinically significant difference of the questionnaires [ 27 29 ]. The information of progression on HRCT was collected from all the HRCTs available during follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…(2) increased fibrosis on HRCT; (3) progressive symptoms, or progressive symptoms and increased fibrosis on HRCT over 24 months despite treatment [26]. The progressive symptoms were defined as increased (SGRQ, SOBQ) or decreased (LCQ) total scores of a minimum clinically significant difference of the questionnaires [27][28][29]. The information of progression on HRCT was collected from all the HRCTs available during follow-up.…”
Section: The Definition Of Disease Progressionmentioning
confidence: 99%
“…Several studies have demonstrated moderate to strong correlations between FVC and patient-reported outcomes at baseline [12,[15][16][17], although other studies have demonstrated weaker correlations [18][19][20]. Taken together, these data suggest that although patient-reported outcomes assess different dimensions of disease than lung function, preserving lung function may be beneficial in preventing deterioration in symptoms and HRQL in patients with PPF.…”
Section: Discussionmentioning
confidence: 85%
“…Although the mechanisms behind the observed effects of nintedanib on worsening of cough and dyspnoea are unknown, analyses of data from the INPULSIS trials in patients with IPF and the SENSCIS trial in patients with systemic sclerosis-associated ILD [ 11 , 12 ], as well as data from observational studies in patients with IPF [ 13 , 14 ], have shown that patients with the greatest declines in FVC have the greatest declines in patient-reported outcomes. Several studies have demonstrated moderate to strong correlations between FVC and patient-reported outcomes at baseline [ 12 , 15 17 ], although other studies have demonstrated weaker correlations [ 18 20 ]. Taken together, these data suggest that although patient-reported outcomes assess different dimensions of disease than lung function, preserving lung function may be beneficial in preventing deterioration in symptoms and HRQoL in patients with PPF.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies had doubtful methodological quality for hypothesis testing on construct validity due to the inclusion of a low number of patients [ 33 ] or removal of outliers without specification [ 37 ]. Lastly, one study had doubtful methodological quality on responsiveness due to use of an inadequate statistical method [ 26 ].…”
Section: Resultsmentioning
confidence: 99%